การผลิตเส้นใยอาหารจากหัวกระเทียม Allium sativum Lin. - สิขรินทร์ ก้อนในเมือง (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research is to study production of dietary fiber from garlic bulb Allium sativum Lin. by removing lipid and carbohydrate from garlic bulb. Lipid was extracted by 2 methods. Amount of 95% Ethanol (ml) per weight of garlic (g) is 3:1 at 48 hours, lipid decreased from 3.42% to 0.51% and S.aureus could resist to antimicrobial activity of garlic, which is known as allicin. Direct steam extraction at 3.5 hours, lipid decreased to 2.55% but S.aureus couldn’t grow in the same culture broth because of antimicrobial activity of allicin remained. The optimum method for extracting lipid was extraction by 95% ethanol. Enzyme ∝-Amylase (Termamyl 120L) was used for getting rid of starch. The optimum pH and activating temperature of this enzyme was 6.9 and 95°∁ that made the highest activity was about 120 units. Studying the condition of using ∝-Amylase by varying the amount of enzyme into 2.5, 5.0, 7.5 and 10.0% (v/v) and digestion time as 12, 24, 36 and 48 hours at the optimum conditions that remaining starch (RS), water holding capacity (WHC), oil absorption capacity (OAC) and water separation (WS) were determined. The results showed RS, WHC and WS were significantly (p˃0.05) decreased in order to the amount of enzyme and time were increased. But OAC was not different (p˃0.05) because the amount of lignin was stable. The product consisted of 85.77% of total dietary fiber, 28.32% of soluble dietary fiber, 32.16% of cellulose, 22.89% of hemicellulose and 2.40% of lignin. Applying to add in bread by varying amount of fiber to 0, 5, 10, 15 and 20% (w/w), sensory evaluation was tested. The results showed that at 10% (w/w) of fiber added got the highest overall acceptance score comparing to other concentration (p˃0.05)